2022
DOI: 10.1109/tnsre.2022.3181252
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer’s Disease Detection Using Comprehensive Analysis of Timed Up and Go Test via Kinect V.2 Camera and Machine Learning

Abstract: — Alzheimer’sdisease (AD) is a progressive neurodegenerative disease affecting cognitive and functional abilities. However, many patients presume lower cognitive or functional abilities because of aging and do not undergo clinical assessments until the symptoms become too advanced. Developing a low-cost and easy-to-use AD detection tool, which can be used in any clinical or non-clinical setting, can enable widespread AD assessments and diagnosis. This paper investigated the feasibility of developing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Additionally, the technique showed that it was possible to differentiate between the three stages of the illness. The study investigated the feasibility of creating a tool to differentiate between AD and HC persons utilizing information from the Timed Up and Go (TUG) test, a straightforward assessment of walking and balance [29]. When conducting the TUG test in front of a Kinect V.2 camera, joint position data from 47 HC and 38 AD individuals was gathered.…”
Section: Unique Mri Formatting For Disease Stagementioning
confidence: 99%
“…Additionally, the technique showed that it was possible to differentiate between the three stages of the illness. The study investigated the feasibility of creating a tool to differentiate between AD and HC persons utilizing information from the Timed Up and Go (TUG) test, a straightforward assessment of walking and balance [29]. When conducting the TUG test in front of a Kinect V.2 camera, joint position data from 47 HC and 38 AD individuals was gathered.…”
Section: Unique Mri Formatting For Disease Stagementioning
confidence: 99%
“…10-fold cross-validation means that when training the model, the trained samples are divided into 10 parts, where 1 part of the data is left to validate the model and the remaining 9 samples are trained. The cross validation is repeated 10 times and the average of the 10 test results is used as the final result [49].…”
Section: A Parameter Setting Of Experimentsmentioning
confidence: 99%
“…Both solutions are not only expensive but also have surgical risks [ 5 ]. Most of the commercially available devices are not in accordance with the World Health Organization's (WHO) ASSURED criteria for Affordable, Sensitive, Specific, User-friendly, Rapid and robust, Equipment-free and Deliverable devices [ [12] , [13] , [14] ]. Therefore, there is a need for a non-invasive solution that can provide continuous and real-time monitoring of parameters related to HF.…”
Section: Introductionmentioning
confidence: 99%